Diversity and inclusion of culturally and linguistically diverse students in K‐12 Chinese language education. (14th July 2022) - Lu, Xinyue; Troyan, Francis John
The Challenge: The Challenge Statement: The inclusion of culturally and linguistically diverse (CLD) students is rarely addressed in Chinese Language Education. What is the potential of Chinese classrooms as sites for the inclusion of CLD students? This article presents findings from a systematic review and suggests a path forward for a more culturally responsive Chinese Language Education. Abstract: Chinese as a world language has gained popularity in US K‐12 education over the past two decades. However, little attention has been paid to diverse populations in Chinese language classrooms and how the students' diverse cultural and linguistic backgrounds influence their experiences in Chinese programs. This article presents a research synthesis that examines cultural and linguistic diversity in US K‐12 Chinese language education research. It reveals the tendency of the field to oversimplify culturally and linguistically diverse (CLD) students into dichotomous groups (i.e., Chinese speaking vs. English speaking) and the inequitable representation of CLD populations as well as the underrepresentation of their experiences in the curriculum. The findings suggest that there is a need for the Chinese language education field to engage in critical conversations on diversity, and to make Chinese language teaching more culturally relevant and sustainable to the diverse populations it serves.